Association between selective serotonin reuptake inhibitors use and blood transfusion risk in older adults after hip fracture: a cohort study - Héloïse Gobillot-Morisson; Bastien Genet; Corinne Frère; Judith Cohen-Bittan; Mathieu Raux; Marie-Eva Rollet; Anthony Meziere; Jacques Boddaert; Lorène Zerah; Sara Thietart (BMC Geriatrics)
Abstract Background Hip fracture is common and associated with high morbidity and mortality rates. Selective serotonin reuptake inhibitors (SSRIs) influence platelet hemostasis and might result in abnormal bleeding. This study aims to determine whether the use of SSRIs in older patients undergoing hip fracture surgery is associated with the risk of perioperative red blood cell (RBC) transfusion. Methods We conducted a retrospective observational study using prospectively collected data of patients aged 70 years and older admitted to a French geriatric perioperative ward for hip fracture between January 2012 and June 2021. The primary endpoint was the occurrence of RBC transfusion during hospitalization. Multivariate logistic regression was performed, with a sensitivity analysis according to co-prescriptions. Results Out of 1085 patients, 253 (23%) were male, mean age was 86 (± 6.2) years, and median Charlson Comorbidity Index was 7 (interquartile range [5–8]). 486 (45%) patients received perioperative RBC transfusion, with a median of 2 units (interquartile range [1–3]) transfused per patient postoperatively. After adjusting for age, sex, comorbidities, functional status, institutionalization, polypharmacy, antiplatelet therapy, fracture type, hemoglobin and albumin levels, the use of SSRIs was not associated with an increased risk of RBC transfusion (aOR 0.91, 95%CI 0.64–1.29, p = 0.59). We did not observe any association between concomitant use of SSRIs and anticoagulant or antiplatelet therapy and the risk of RBC transfusion. Conclusions Among older comorbid adults undergoing hip fracture surgery, the use of SSRIs was not associated with an increased risk of perioperative RBC transfusion.